POLA KOMUNIKASI KOMUNITAS MOBIL "LOWBUDGED SUKOHARJO" DALAM MEMPERTAHANKAN SOLIDARITAS KELOMPOK - Adam Mardani, Anggeswara (Solidaritas, 2025)
Automotive communities in Indonesia not only serve as a platform for sharing information about vehicles but also as a means of fostering solidarity among members. One of the most notable communities is the "Lowbudged Sukoharjo" car community, which stands out for its unique characteristic of accepting various types and brands of cars without distinguishing their quality or prestige. However, as the number of members grows and their backgrounds become more diverse, this community faces challenges in maintaining solidarity and effective communication. Differences in perspectives, members' busy schedules, and potential miscommunication pose obstacles that can reduce the cohesion within the community. Despite these challenges, the community remains committed to promoting a sense of family and passion for car modification, while actively participating in social activities in the Sukoharjo area. This study aims to analyze the communication patterns within the "Lowbudged Sukoharjo" car community in maintaining group solidarity. A qualitative approach was employed in this research using participatory observation, in-depth interviews, and document analysis. Redding and Sanborn’s organizational communication theory serves as the theoretical foundation, emphasizing the importance of information dissemination and reception within an interdependent network of relationships. The findings reveal that the Lowbudged Sukoharjo community applies two main communication patterns to maintain its solidarity: the wheel pattern and the all-channel pattern. The wheel pattern is used in structured communication, where the community leader acts as the central hub of information and coordinates various community activities, such as event planning and decision-making. Meanwhile, the all-channel pattern is utilized in daily communication among members, mainly through WhatsApp groups and face-to-face meetings, allowing members to interact directly without intermediaries. The combination of these two patterns enables the community to maintain organizational order while fostering openness and closeness among members. Keywords: Communication pattern, wheel pattern, all-channel pattern, car community, group solidari ty